Presence of donor specific HLA class 2 antibodies (DSA class 2) is associated with development of graft fibrosis more than 10 years after liver transplantation–a retrospective single center study. Issue 7 (18th May 2021) - Sultani, Bejan; Marget, Matthias; Briem‐Richter, Andrea; Herrmann, Jochen; Meisner, Sebastian; Grabhorn, Enke Freya; Ozga, Ann‐Kathrin; Weidemann, Sören; Herden, Uta; Fischer, Lutz; Sterneck, Martina
Abstract: Here the impact of donor specific human leukocyte antigen (HLA) class 2 antibodies (DSA cl 2) on long term outcome after liver transplantation (LT) was investigated. Altogether 156 (44 pediatric and 112 adult) LT recipients were included in the study. Graft fibrosis was assessed by liver elastography and biopsy. DSA cl 2 were determined by Luminex technology. 46% of LT recipients were positive for DSA cl 2 after a median follow‐up of 15 years. In the multivariate analysis DSA cl 2 were significantly associated with immunosuppressive monotherapy (OR 5.42; 95% CI: 1.02–28.90; p = .048). Compared to DSA cl 2 negative patients, positive recipients had significantly more graft fibrosis based on the liver stiffness (mean 9.4 ± 9.0 kPa vs. 6.5 ± 6.3 kPa; p < .002) and fibrosis stages determined by liver elastography ( p = .016) and the performed liver biopsies ( p = .002). Also, a significantly higher incidence of chronic rejections (11% vs. 2%; p = .045) and graft losses (6% vs. 0%; p = .043) were found. In the multivariate regression analysis DSA cl 2 were significantly associated with graft fibrosis (OR 4.57; 95% CI 1.59–13.10; p = .005). So, these data suggest that development of DSA cl 2 occurs more often with immunosuppressive monotherapy and may ultimately result in chronic rejection and graft fibrosis.